The Sea-girt Fortress: A Story of Heligoland - Westerman, Percy F. (Percy Francis), 1876-1959; Wigfull, W. Edward (William Edward), 1875-1944 (Salt Lake City, UT : Project Gutenberg, 2015)
"The Sea-girt Fortress: A Story of Heligoland" by Percy F. Westerman is an adventure novel likely written in the early 20th century. The narrative follows two young sailors, Sub-Lieutenant Jack Hamerton and his American friend Oswald Detroit, as they embark on a cruise to Kiel on their yacht, the "Diomeda". However, their voyage takes an unexpected turn when they accidentally enter a prohibited naval area near the fortified island of Heligoland, leading to their arrest by German authorities on suspicion of espionage. The opening of the story introduces readers to the main characters aboard their yacht, setting the stage for their adventure. As they navigate foggy waters, they rescue a sailor who has fallen overboard from a German destroyer, illustrating their bravery and quick thinking. However, their luck quickly changes as they inadvertently find themselves tangled in a web of international intrigue when they are arrested by German naval officers. The narrative hints at the escalating tension of their predicament, with a multitude of potential consequences and encounters with naval warfare that lie ahead. (This is an automatically generated summary.)
Release date is 2015-09-24
Produced by R.G.P.M. van Giesen. Thank you, Iain Somerville!
Keywords: War stories; World War, 1914-1918 -- Naval operations -- Juvenile fiction; Helgoland (Germany) -- Juvenile fiction